2015
DOI: 10.2196/jmir.4384
|View full text |Cite
|
Sign up to set email alerts
|

Swab2know: An HIV-Testing Strategy Using Oral Fluid Samples and Online Communication of Test Results for Men Who Have Sex With Men in Belgium

Abstract: BackgroundAs HIV remains a public health concern, increased testing among those at risk for HIV acquisition is important. Men who have sex with men (MSM) are the most important group for targeted HIV testing in Europe. Several new strategies have been developed and implemented to increase HIV-testing uptake in this group, among them the Swab2know project.ObjectiveIn this project, we aim to assess the acceptability and feasibility of outreach and online HIV testing using oral fluid samples as well as Web-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 36 publications
(40 reference statements)
5
53
1
2
Order By: Relevance
“…Twenty studies provided non‐targeted testing to the general population, while 44 studies provided testing to one or more groups at higher risk of HIV infection. MSM were the group most frequently targeted ( n = 31) , followed by: migrants ( n = 10) , people who use/inject drugs (PWUD/PWID) ( n = 8) , SWs ( n = 7) , black and minority ethnic groups (BME) ( n = 5) , young people ( n = 4) , homeless people ( n = 3) , and other key risk populations not specified ( n = 3) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty studies provided non‐targeted testing to the general population, while 44 studies provided testing to one or more groups at higher risk of HIV infection. MSM were the group most frequently targeted ( n = 31) , followed by: migrants ( n = 10) , people who use/inject drugs (PWUD/PWID) ( n = 8) , SWs ( n = 7) , black and minority ethnic groups (BME) ( n = 5) , young people ( n = 4) , homeless people ( n = 3) , and other key risk populations not specified ( n = 3) .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 65 studies that introduced HIV testing, 56 studies utilized novel HIV testing technologies to improve testing uptake [18,19,[21][22][23][25][26][27]29,[31][32][33][34][35][36][37][38][39][41][42][43]46,47,[50][51][52]54,[58][59][60][61][62][64][65][66][67][68][69][72][73][74][75][76][77][78]81,83,84,[86][87][88][89]…”
Section: Testing Provision Outside Of Health Care Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of the article collection process is presented in the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) Flow Diagram in Figure . A total of 27 articles were excluded because the mean sample age was ≥30 years .…”
Section: Resultsmentioning
confidence: 99%
“…technical reports in the grey literature; non‐English peer‐reviewed publications) are not accounted for in our review. Third, because our inclusion criteria required a sample of at least 50% gbMSM under 30 years of age, studies that may have reported relevant findings about online intervention with gbMSM are excluded ; future analyses of these studies will provide important details about the experiences of older generations of gbMSM with online interventions. Nevertheless, these findings provide a key “first step” in informing both potentially effective strategies and a renewed research agenda regarding the development of evidence‐based online interventions to address HIV/STBBIs among young gbMSM.…”
Section: Discussionmentioning
confidence: 99%